Smartphone usage and addiction among nursing students in Universiti Malaysia Sabah - Segaran Ramodran; Lenny Seputri Masse; Nurul Hanis Syazwan Irawan; Suhailah Saniman (Malaysian Journal of Medicine and Health Sciences, 2020)
Smartphone has become an essential Smart-tool for IT-based learning among university students. However, excessive use of smartphones can be addictive leading to psychological distress, poor academic performance, social isolation and depression. In the context of University Malaysia Sabah (UMS), the issue of contention is whether smartphone addiction is a problem among nursing undergraduate students and thus the justification for this study. This study evaluated the pattern of usage smartphone and addiction among nursing students in UMS. Methods: The study deployed a cross-sectional survey design involving 100 (N) respondents selected through clustered convenient sampling from year 1(n=35), year 2 (n=35) and year 3 (n=30) nursing students who are currently pursuing their diploma study in UMS. Ethical approval was obtained from the Research Ethics Committee of UMS as well-informed consent from respondents. The study tool consisted of a well-establish validated questionnaire benchmarked from a previous study (reliability Cronbach α= 0.78) which captured respondents’ socio-demographics, smartphone usage characteristic proforma and Smart Addiction Scale (SAS). Results: Among 100 nursing students in this study, 78% (n=78) of them had high smartphone usage averaging 4.3 hours daily. The overall prevalence of smartphone addiction among nursing students in this study was 25% (n=25). Male student nurses significantly had higher smartphone addiction scores compared to female students (p=0.01). Likewise, year 3 students had higher addiction scores compared to their peers in year 2 or year 1 (p=0.002). Conclusion: findings from this study imply that smartphone addiction affects 1 in 4 nursing students in UMS and there is a need to develop ‘digital detox” strategies to address the issue.